The rise and stagnation of Chile's export cycle - Sossdorf, Fernando (Latin American Journal of Trade Policy, 2024)
Chile's international insertion strategy has been a critical driver of economic growth since the 1970s. However, real exports of goods and services have lost dynamism in the last two decades. Therefore, this article argues that such deceleration is due to the stagnation of the export cycle, given the liberal narrative in which Chile, a country endowed with natural resources, should specialize according to its static comparative advantages and assign a subsidiary role to the State. Indeed, the evidence for Chile shows that a long-term export cycle based on natural resources not complemented by industrial policies leads to specialization in export sectors with low technological dynamism. Chile's international insertion in the global economy also has limited exports to a few products, destination markets, and firms. To diversify exports, Chile needs to move towards more technology-intensive sectors and more dynamic in terms of demand in world markets. To the extent that exports become more concentrated in these sectors, there will be a greater likelihood that innovation and productivity will occur at higher rates, boosting Chile's long-term economic growth.